EGR1, EGFR and IGF1R protein expressions in non-small cell lung cancer and their clinical significances - Yu, Dujuan; Tan, Ping; Yu, Min; Shi, Shaomin; Wang, Xue (Bangladesh Journal of Pharmacology, 2016)
The purpose of this study was to investigate the incidence and clinical significance of alterations in EGFR, IGF1R and the cell signaling pathway activities induced by them, as well as EGR1 expression in resected non-small cell lung cancer (NSCLC). The protein expressions of biomarker were evaluated by Western blotting in tissues from 19 surgically resected NSCLCs. High expressions of EGR1, EGFR and IGF1R were detected in more than 30% tumor tissues. High expressions of pErk and pAkt were detected in more than 50% paracancer tissues. There were significant correlations between the NSCLC target factors detected (p<0.05). Alterations of protein expressions of target factor detected in NSCLC were significantly associated with alterations in pathological subtype, differentiation, pathological stage, and smoking history. Positive EGR1 might be associated with good survival, while positive pErk might be associated with poor prognosis.